Relative Validity and Reproducibility of a Semi-Quantitative Food Frequency Questionnaire for Determining Nutrient Intake in Older Adults in New Zealand: The REACH Study - Yu AD; Mumme KD; Conlon CA; von Hurst PR; Gillies N; Heath A-L; Coad J; Beck KL (MDPI (Basel, Switzerland), 2022)
Dietary intake is an important predictor of health and disease outcomes. This cross-sectional study evaluated the relative validity and reproducibility of a semi-quantitative food frequency questionnaire (FFQ) for assessing energy and nutrient intake in older adults. Dietary data were collected 2018-2019 in Auckland, New Zealand from a convenience sample of community-dwelling adults (65-74 years, n = 294, 37% male) using a 109-item self-administered FFQ at baseline (FFQ1) and four weeks later to assess reproducibility. FFQ1 was compared to a four-day food record to determine relative validity. Agreement between dietary assessment tools was assessed for both raw and energy-adjusted nutrient intakes using paired t-tests, correlation coefficients, weighted kappa statistic, Bland-Altman plots, and linear regression analysis. Energy adjustments moderately improved the relative validity and reproducibility for most nutrients. For energy and energy-adjusted nutrient intakes, the mean correlation coefficients were 0.38 (validity) and 0.65 (reproducibility); the mean weighted kappa statistics were 0.27 (validity) and 0.51 (reproducibility). A significant slope of bias was present in 54% (validity) and 25% (reproducibility) of Bland-Altman plots. The Researching Eating, Activity, and Cognitive Health (REACH) FFQ has acceptable relative validity and good reproducibility for ranking nutrient intakes in older New Zealand adults, but is less suitable for assessing absolute nutrient intakes.
Copyright: © 2022 by the authors.
Keywords: dietary assessment tool; food diary; food frequency questionnaire; macronutrient intake; micronutrient intake; nutrition assessment; validation; Aged; Cross-Sectional Studies; Eating; Female; Humans; Male; New Zealand; Reproducibility of Results; Surveys and Questionnaires